Biodiesel from microalgae: A critical evaluation from laboratory to large scale production - Rawat, I.; Ranjith Kumar, R.; Mutanda, T.; Bux, F. (Applied energy, 2013)
The economically significant production of carbon-neutral biodiesel from microalgae has been hailed as the ultimate alternative to depleting resources of petro-diesel due to its high cellular concentration of lipids, resources and economic sustainability and overall potential advantages over other sources of biofuels. Pertinent questions however need to be answered on the commercial viability of large scale production of biodiesel from microalgae. Vital steps need to be critically analysed at each stage. Isolation of microalgae should be based on the question of whether marine or freshwater microalgae, cultures from collections or indigenous wild types are best suited for large scale production. Furthermore, the determination of initial sampling points play a pivotal role in the determination of strain selection as well as strain viability. The screening process should identify, purify and select lipid producing strains. Are natural strains or stressed strains higher in lipid productivity? The synergistic interactions that occur naturally between algae and other microorganisms cannot be ignored. A lot of literature is available on the downstream processing of microalgae but a few reports are available on the upstream processing of microalgae for biomass and lipid production for biodiesel production. We present in this review an empirical and critical analysis on the potential of translating research findings from laboratory scale trials to full scale application. The move from laboratory to large scale microalgal cultivation requires careful planning. It is imperative to do extensive pre-pilot demonstration trials and formulate a suitable trajectory for possible data extrapolation for large scale experimental designs. The pros and cons of the two widely used methods for growing microalgae by photobioreactors or open raceway ponds are discussed in detail. In addition, current methods for biomass harvesting and lipid extraction are critically evaluated. This would be novel approach to economical biodiesel production from microalgae in the near future. Globally, microalgae are largest biomass producers having higher neutral lipid content outcompeting terrestrial plants for biofuel production. However, the viscosities of microalgal oils are usually higher than that of petroleum diesel.